Culturally transmitted paternity beliefs and the evolution of human mating behaviour - Mesoudi, Alex (The Royal Society, 2007)
Recent anthropological findings document how certain lowland South American societies hold beliefs in ‘partible paternity’, which allow children to have more than one ‘biological’ father. This contrasts with Western beliefs in ‘singular paternity’, and biological reality, where children have just one father. Here, mathematical models are used to explore the coevolution of paternity beliefs and the genetic variation underlying human mating behaviour. A gene–culture coevolutionary model found that populations exposed to a range of selection regimes typically converge on one of two simultaneously stable equilibria; one where the population is monogamous and believes in singular paternity, and the other where the population is polygamous and believes in partible paternity. A second agent-based model, with alternative assumptions regarding the formation of mating consortships, broadly replicated this finding in populations with a strongly female-biased sex ratio, consistent with evidence for high adult male mortality in the region. This supports an evolutionary scenario in which ancestral South American populations with differing paternity beliefs were subject to divergent selection on genetically influenced mating behaviour, facilitated by a female-biased sex ratio, leading to the present-day associations of female control, partible paternity and polygamy in some societies, and male control, singular paternity and monogamy in others.